Small RNA Profiles of the Rice PTGMS Line Wuxiang S Reveal miRNAs Involved in Fertility Transition - Zhang, Hongyuan; Hu, Jihong; Qian, Qian; Chen, Hao; Jin, Jing; Ding, Yi (Frontiers in Plant Science, 2016)
MicroRNAs (miRNAs) play key roles in the regulation of plant growth and developmental processes. In this study, the RNA-seq technique was employed to examine the expression profiles of miRNAs in a novel rice photo-thermo sensitive generic male sterile (PTGMS) line Wuxiang S (WXS) during the fertility transition. A total of 497 known miRNAs and 273 novel miRNAs were identified. By means of the differentially expression analysis, a total of 26 miRNAs were discovered to be significant difference expression between WXS (Sterility, S) and WXS (Fertility, F). And some of these miRNAs were validated by quantitative real-time PCR. Among these miRNAs, eleven of which were decreased, and fifteen of which were increased in the expression levels of genes when WXS (S) compared with WXS (F), respectively. Some of these miRNAs such as osa-miR156a-j, osa-miR164d and osa-miR528, were showed to be negatively correlated with their targets. These targets have previously been reported to be related with pollen development and male sterility, suggesting that these miRNAs might be involved in the regulation of pollen development in the rice PTGMS line WXS. Furthermore, the miRNAs editing events were also observed. A possible control model of miRNAs and signaling pathway was proposed in the process of fertility transition of rice PTGMS line WXS in this study. These findings contribute to our understanding of the roles of miRNAs during anther development of PTGMS occurrence in rice.